QUALITY CONTROL MEASUREMENT AND IN VITRO BIOEQUIVALENCE OF VALSARTAN AND ATENOLOL TABLETS MARKETED IN UKRAINE - K. Y. Peleshok (International Journal of Medicine and Medical Research, 2021)
Background. The urgent issue of hypertension is determined by its high population incidence, significant burden of the disease, risk of disability and impact on life expectancy. Rational combinations of drugs of different pharmacological groups in case of ineffectiveness of monotherapy to achieve the clinical effect of pharmacotherapy are clearly recommended in the world and national recommendations for diagnosis and treatment of hypertension. Therefore, innovative pharmaceutical development of a combination of antihypertensive drugs and creation of domestic drugs with antihypertensive action is an urgent task of contemporary pharmacy.